AKIBAT HUKUM TERHADAP KREDITUR SEPARATIS DALAM PENGURUSAN DAN PEMBERESAN HARTA PAILIT PASCA PUTUSAN MAHKAMAH KONSTITUSI NO. 67/PUU-XI 2013 - Fatimah Islamy Nasution; Budiman Ginting; Sunarmi Sunarmi; Dedi Harianto (USU LAW JOURNAL, 2018)
Abstract The decision of Constitutional Court No. 67 / PUU-XI / 2013 which has been issued granted article 95 chapter 4 specified in the Indonesia Labour law to minimum wages, causing the position of the separatist creditor in the process of fixing and ordering Boedel bankruptcy changed that the previous division of separatist creditors' Boedel bankruptcy property of having the privilege to be the first part.The rule has resulted in the Court's decision of the precedence to transfer it to the power as a preferred creditor. The situation has a legal effect on the parties involved in managing and securing assets bankruptcy.  The research that will be described in this thesis: How the position of Separatist Creditors before the decision of Constitutional Court, What is the legal effect to the separatist creditor after the decision of Constitutional Court number 67 / PUU XI / 2013, How is the application in handling and securing against the separatist creditor after the decision of Constitutional Court number 67 / PUU-XI / 2013. The research is conducted to explain and analyze the legal effect of the separatist creditor in the management and disposition of the property bankruptcy after the decision of Constitutional Court number 67 / PUU-XI / 2013. The results indicate the issuance of the decision of Supreme Court number 67 / PUU-XI / 2013, The legal consequences of the separatist Creditor after the decision of Constitutional Court in the fulfillment of its rights no longer precedence as has been done, that is the decision of Constitutional Court when a bankruptcy takes place whereas the fulfillment of its right is a separatist Creditor as the party that lends the capital.However the position of the separatist Creditor after the decision of Constitutional Court who initially came to be shifted to the workers because in the event of bankruptcy is often the most disadvantaged party to the laborer as in addition to its weak position in the bankruptcy process is also very dependent on the salary life earned from companies that bankrupt where the company is, the position of Separatist creditors who were formerly higher than the recent minimum wages.The conclusion is to get their payments receivable as wages; a worker has the right to predate a secured creditor. Keywords: bankruptcy, separatist creditors, workers' wages.